Opportunities to Increase Soil Carbon Stocks Under Climate Change Conditions - Khakimova, M.; Buriyeva, S. Z. (American Journal of Biology and Natural Sciences, 2026)
This paper discusses the two challenges, i.e., how agriculture could effectively achieve carbon neutrality and what kind of supporting strategies could be developed, as these foreign scholars failing to feature in the dedicated studies on this issue has been reviewed and presented here. Methods for achieving carbon neutrality by enhancing soil productivity, mitigating emissions, and establishing sustainable agroecosystems in the context of climate change are examined. The agrochemical characteristics of light gray soils in the research field are also analyzed. Also analyzed are projects for the environment implemented in the Republic of Uzbekistan and, specifically policies of the state to address soil degradation and carbon release. Scientific findings in the breeding of climate-resilient crops and stabilizing agricultural systems are provided as one of the most important weather changes adaptation strategies. The article adds that carbon-neutral agriculture is key to avoiding global environmental issues.